A study of concrete slabs with steel wire mesh reinforcement under close-in explosive loads. (December 2017) - Li, Jun; Wu, Chengqing; Hao, Hong; Su, Yu; Li, Zhong-Xian
Highlights: Concrete with fibre reinforcement shows better strength and ductility. Hybrid steel wire mesh and steel fibre reinforcement improves beam shear capacity. Beam with hybrid reinforcement shows exceptional energy absorption capacity. Slab with hybrid reinforcement survives 12 kg TNT detonation at 1.5 m standoff distance. Numerical model confirms the charge shape effect in the blast tests. Abstract: Structural responses and damages under blast loading environments are critical to structural and personnel safety. The blast scenarios involving close-in detonations are attracting increasingly more attentions over the last few decades due to the rising of terrorism. Under close-in detonations, structural elements tend to fail in a brittle mode including shear, concrete crater and spall. In such loading scenarios, the structural designated loading capacity which is usually based on flexural deformation assumption is not fully developed. To provide high-level structural protection, high performance concretes with varying fibre additions are now widely investigated and used in blast resistance designs. In the present study, field blast tests results on reinforced concrete slabs under close-in detonations are presented. Performances of slabs made of normal strength concrete and steel fibre reinforced concrete are compared and discussed. Besides conventional steel rebar reinforcement, new reinforcement scheme i.e. hybrid steel wire mesh-micro steel fibre reinforcement is investigated through the laboratory static tests and field blast tests. Furthermore, a numerical study based on Multi-Material ALE and Lagrangian algorithm is carried out to further investigate the field tests' phenomenon.